Biochemical diagnosis of ventricular dysfunction in elderly patients in general practice: observational study. Issue 7239 (1st April 2000) - Smith, H; Pickering, R M; Struthers, A; Simpson, I; Mant, D
Abstract: Objective: To investigate the usefulness of measuring plasma concentrations of B type natriuretic peptide in the diagnosis of left ventricular systolic dysfunction in an unselected group of elderly people. Design: Observational study. Setting: General practice with four centres in Poole, Dorset. Participants: 155 elderly patients aged 70 to 84 years. Main outcome measures: Diagnostic characteristics of plasma B type natriuretic peptide measured by radioimmunoassay as a test for left ventricular systolic dysfunction assessed by echocardiography. Results: The median plasma concentration of B type natriuretic peptide was 39.3 pmol/l in patients with left ventricular systolic dysfunction and 15.8 pmol/l in those with normal function. The proportional area under the receiver operator curve was 0.85. At a cut-off point of 18.7 pmol/l the test sensitivity was 92% and the predictive value 18%. Conclusions: Plasma concentration of B type natriuretic peptide could be used effectively as an initial test in a community screening programme and, possibly, using a low cut-off point, as a means of ruling out left ventricular systolic dysfunction. It is, however, not a good test to "rule in" the diagnosis, and access to echocardiography remains essential for general practitioners to diagnose heart failure early.